Comparison of capsule and posterior lumbar interbody fusion in cauda equina syndrome with retention: a 24-month follow-up study - Li, Fudong; Ji, Chenglong; Han, Linhui; Sun, Jingchuan; Sun, Kaiqiang; Shi, Jiangang; Zhang, Bin (European journal of medical research, 2024)
Cauda equina syndrome with retention (CESR) is a severe lumbar condition characterized by painless urine retention due to cauda equina nerve injury. The standard treatment, posterior lumbar interbody fusion (PLIF), often yields suboptimal results. This study aims to compare the clinical safety and efficacy of a novel technique, capsule lumbar interbody fusion (CLIF), with PLIF in CESR patients, hypothesizing that CLIF can enhance neurological recovery by reducing nerve tension. A single-center, retrospective study was conducted on 83 patients with CESR due to lumbar disc herniation, who underwent either PLIF (n = 44) or CLIF (n = 39). Patients were assessed preoperatively and at 3, 12, and 24 months postoperatively using the Oswestry Disability Index (ODI), Visual Analogue Scale (VAS), International Consultation on Incontinence Questionnaire Short Form (ICI-Q-SF), and Rintala score. Urodynamic studies and nerve tension measurements were also performed. Statistical analysis included t tests, Mann-Whitney U tests, and Spearman's correlation. Both groups showed significant postoperative improvements, but the CLIF group had superior outcomes. At 12 months, the CLIF group had lower VAS scores (1.15 ± 0.84 vs. 1.68 ± 0.60, p = 0.001) and ODI scores (23.31 ± 7.51 vs. 28.30 ± 8.26, p = 0.005). At 24 months, the CLIF group continued to show better results with ODI scores (15.97 ± 6.43 vs. 22.11 ± 6.41, p < 0.001) and higher ODI recovery rates (60.41 ± 17.6% vs. 44.71 ± 18.99%, p < 0.001). The CLIF group also had better ICI-Q-SF scores (2.13 ± 1.23 vs. 3.02 ± 1.45, p = 0.004) and Rintala scores (17.97 ± 1.43 vs. 16.59 ± 1.54, p < 0.001). Lower postoperative nerve tension in the CLIF group correlated with these improved outcomes. CLIF demonstrated superior efficacy over PLIF in treating CESR, with significant improvements in pain relief, functional recovery, and bladder and bowel function. This study highlights the potential of CLIF as a more effective surgical option for CESR, emphasizing its importance in improving patient outcomes and reducing the burden of CESR on patients and society.